2008
DOI: 10.1074/jbc.c800040200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Squid Rhodopsin with Intracellularly Extended Cytoplasmic Region

Abstract: G-protein-coupled receptors play a key step in cellular signal transduction cascades by transducing various extracellular signals via G-proteins. Rhodopsin is a prototypical G-protein-coupled receptor involved in the retinal visual signaling cascade. We determined the structure of squid rhodopsin at 3.7 Å resolution, which transduces signals through the G q protein to the phosphoinositol cascade. The structure showed seven transmembrane helices and an amphipathic helix H8 has similar geometry to structures fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 32 publications
2
130
0
Order By: Relevance
“…The helix 8 region of GPCRs forms an amphipathic helix that lies parallel to the plasma membrane and is anchored by palmitoylated cysteine groups (Palczewski et al, 2000;Shimamura et al, 2008). Helix 8 is believed to move upon receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…The helix 8 region of GPCRs forms an amphipathic helix that lies parallel to the plasma membrane and is anchored by palmitoylated cysteine groups (Palczewski et al, 2000;Shimamura et al, 2008). Helix 8 is believed to move upon receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of G proteins have been obtained in both active and inactive states (4)(5)(6), and structures of bovine rhodopsin (7)(8)(9)(10)(11)(12), squid rhodopsin (13,14), bovine opsin (15,16), the human ␤ 2 AR (17)(18)(19), the turkey ␤ 1 AR (20), and the adenosine A2a receptor (21) have been reported. However, relatively little is known about the active-state GPCR-G protein complex.…”
mentioning
confidence: 99%
“…The crystal structures of bovine and squid rhodopsins 16,29,30) suggested that the Arg3.50 in the inactive state forms salt bond with the adjacent Glu or Asp3.49 residue of TMH III. Upon mutation of the adjacent Glu or Asp3.49, the arginine3.50 residue will be released from the electronic constraint leading to a conformational change (Fig.…”
Section: Discussionmentioning
confidence: 99%